2017
DOI: 10.1002/brb3.895
|View full text |Cite
|
Sign up to set email alerts
|

Consistent hypersocial behavior in mice carrying a deletion of Gtf2i but no evidence of hyposocial behavior with Gtf2i duplication: Implications for Williams–Beuren syndrome and autism spectrum disorder

Abstract: IntroductionWilliams–Beuren syndrome (WBS) is a developmental disorder caused by hemizygous deletion of human chromosome 7q11.23. Hypersocial behavior is one symptom of WBS and contrasts with hyposociality observed in autism spectrum disorder (ASD). Interestingly, duplications of 7q11.23 have been associated with ASD. The social phenotype of WBS has been linked to GTF2I or general transcription factor IIi (TFII‐I). Duplication of GTF2I has also been associated with ASD.MethodsWe compared mice having either a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Behavioral phenotyping of the A350V IQSEC2 mice demonstrates increased locomotion, abnormal social interactions and learning impairments in the absence of motor coordination deficits. The increased preference for social novelty in the A350V mice described here, while different from what has been described in autism, has been described in other genetic encephalopathies with intellectual disability and abnormal social functioning such as Williams’s syndrome (Martin et al, 2018; Ng et al, 2018). Our behavioral findings in the A350V mice appear to model some of the abnormal behaviors found in the human index case with the A350V mutation, specifically hyperactivity, abnormal social interactions with no inhibitions with strangers and impaired cognitive function.…”
Section: Discussionsupporting
confidence: 44%
“…Behavioral phenotyping of the A350V IQSEC2 mice demonstrates increased locomotion, abnormal social interactions and learning impairments in the absence of motor coordination deficits. The increased preference for social novelty in the A350V mice described here, while different from what has been described in autism, has been described in other genetic encephalopathies with intellectual disability and abnormal social functioning such as Williams’s syndrome (Martin et al, 2018; Ng et al, 2018). Our behavioral findings in the A350V mice appear to model some of the abnormal behaviors found in the human index case with the A350V mutation, specifically hyperactivity, abnormal social interactions with no inhibitions with strangers and impaired cognitive function.…”
Section: Discussionsupporting
confidence: 44%
“…GTF2I gene encodes transcription factor TFII‐I, which acts as an inducible multifunctional transcription factor in the nucleus (Danoff, Taylor, Blackshaw, & Desiderio, ; Roy, ) and as a regulator of agonist‐induced calcium entry in the cytoplasm (Caraveo et al., ). Loss of GTF2I led to a negative effect on neurocognitive and behavioral profiles (Chailangkarn, Noree, & Muotri, ; Martin, Iceberg, & Allaf, ; Morris et al., ), but prenatal assessment of functional lesions is not possible. NCF1 gene encodes a component of the NADPH oxidase complex.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models that are haploinsufficient for only Gtf2i have shown in the three-chamber approach task that after eight minutes WT animals investigate a novel object the same amount as a social stimulus, but the Gtf2i mutants still have a significant preference suggesting a lack of habituation (33). In another Gtf2i model, Martin et al compared animals with one, two, three, and four copies of Gtf2i in the three-chamber social approach task, and showed that only animals with one and three copies of Gtf2i displayed a significant preference for the social stimulus (36), but WT animals did not. These three-chamber social approach tests are interpreting a lack of significance as evidence for increased social behavior and not directly comparing the levels of investigation between genotypes (52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, newer tasks, such as social operant tasks that test motivation to receive a social stimulus may more directly test the aspects of social behavior that are affected in WS. This task has been performed on Gtf2i mutants and mice that have only one copy of Gtf2i will work harder to receive a social reward (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation